Syntheses of Cyclomarins – Interesting Marine Natural Products with Distinct Mode of Action towards Malaria and Tuberculosis - Kiefer, Alexander; Kazmaier, Uli (Synthesis, 2019)
The cyclomarins are cyclic heptapeptides from marine streptomycetes containing four rather unusual amino acids. Interestingly, the cyclomarins address two completely different targets: ClpC1, a subunit of the caseinolytic protease of Mycobacterium tuberculosis (MTB), as well as PfAp3Aase of Plasmodium falciparum. Therefore, the cyclomarins are interesting lead structures for the development of drugs targeting tuberculosis and malaria. As a result, several synthetic protocols towards the synthesis of these unusual building blocks as well as the natural products themselves have been developed, which will be discussed in this review.1 Introduction2 Synthesis of the Building Blocks3 Total Synthesis of Cyclomarin C by Yao and Co-workers4 Total Synthesis of Cyclomarin A and C by Barbie and Kazmaier5 Conclusion
Keywords: natural products; cyclopeptides; cyclomarins; total synthesis; malaria; tuberculosis